Intranasal trans-sialidase-based vaccine against Trypanosoma cruzi triggers a mixed cytokine profile in the nasopharynx-associated lymphoid tissue and confers local and systemic immunogenicity - Pacini, María Florencia (2023)
Trypanosoma cruzi, the agent of Chagas disease, can infect through conjunctive or oral mucosas. Therefore, the induction of mucosal immunity by vaccination is relevant not only to trigger local protection but also to stimulate both humoral and cell-mediated responses in systemic sites to control parasite dissemination. In a previous study, we demonstrated that a nasal vaccine based on a Trans-sialidase (TS) fragment plus the mucosal STING agonist c-di-AMP, was highly immunogenic and elicited prophylactic capacity. However, the immune profile induced by TS-based nasal vaccines at the nasopharyngeal-associated lymphoid tissue (NALT), the target site of nasal immunization, remains unknown. Hence, we analyzed the NALT cytokine expression generated by a TS-based vaccine plus c-di-AMP (TSdA+c-di-AMP) and their association with mucosal and systemic immunogenicity. The vaccine was administered intranasally, in 3 doses separated by 15 days each other. Control groups received TSdA, c-di-AMP, or the vehicle in a similar schedule. We demonstrated that female BALB/c mice immunized intranasally with TSdA+c-di-AMP boosted NALT expression of IFN-γ and IL-6, as well as IFN-β and TGF-β. TSdA+c-di-AMP increased TSdA-specific IgA secretion in the nasal passages and also in the distal intestinal mucosa. Moreover, T and B-lymphocytes from NALT-draining cervical lymph nodes and spleen showed an intense proliferation after ex-vivo stimulation with TSdA. Intranasal administration of TSdA+c-di-AMP provokes an enhancement of TSdA-specific IgG2a and IgG1 plasma antibodies, accompanied by an increase IgG2a/IgG1 ratio, indicative of a Th1-biased profile. In addition, immune plasma derived from TSdA+c-di-AMP vaccinated mice exhibit in-vivo and ex-vivo protective capacity. Lastly, TSdA+c-di-AMP nasal vaccine also promotes intense footpad swelling after local TSdA challenge. Our data support that TSdA+c-di-AMP nasal vaccine triggers a NALT mixed pattern of cytokines that were clearly associated with an evident mucosal and systemic immunogenicity. These data are useful for further understanding the immune responses elicited by the NALT following intranasal immunization and the rational design of TS-based vaccination strategies for prophylaxis against T. cruzi.